Penetration of Isavuconazole in Ascites Fluid of Critically Ill Patients - Tobias Lahmer; Gonzalo Batres Baires; Roland M. Schmid; Johannes R. Wiessner; Jörg Ulrich; Maximilian Reichert; Wolfgang Huber; Fritz Sörgel; Martina Kinzig; Sebastian Rasch; Ulrich Mayr (Journal of Fungi, 2021)
Fungal peritonitis is a life-threatening condition which is not only difficult to diagnose, but also to treat. Following recent guidelines, echinocandins and azoles are the recommended antimycotics for the management of intra-abdominal Candida spp. infections, with a favor for echinocandins in critically ill patients. However, the new extended spectrum triazole isavuconazole also has a broad spectrum against Candida spp. Data on its target-site penetration are sparse. Therefore, we assessed isavuconazole concentrations and penetration ratios in ascites fluid of critically ill patients. Obtaining of Isavuconazole plasma and ascites fluid levels as well penetration ratios using paracentesis in critically ill patients. Isavuconazole concentrations were quantified in human plasma and ascites by a liquid chromatography/tandem mass spectrometry (LC-MS/MS) method. Isavuconazole concentrations in plasma and ascites fluid were measured in sixteen critically ill patients. Isavuconazol levels in ascites fluid (1.06 µg/mL) were lower than plasma levels (3.08 µg/mL). Penetration ratio was 36%. In two out of sixteen patients, Candida spp., in detail C. glabrata and C. tropicalis, could be isolated. Cmax/MIC Ratio in plasma of 560 for C. glabrata and 2166 for C. tropicalis could be observed. Following our results, isavuconazole penetrates into ascites. Successful treatment in Candida spp. peritonitis depends on pathogen susceptibility.